Investigating Affective Responses to Remotely Delivered “At Home” Low Volume High Intensity Interval Exercise: A Non-Randomized Parallel Group Feasibility Study - Howard, Imogen; Niven, Ailsa; Kelly, Paul; Phillips, Shaun M. (Frontiers in Sports and Active Living, 2022)
Background Low volume-high intensity interval exercise (LV-HIIE) has gained interest, due to its efficiency in invoking health and fitness benefits. However, little research has studied “at home” feasibility or effects of LV-HIIE. This study aimed to demonstrate that remote “at-home” LV-HIIE research is possible and to investigate if affective responses to the LV-HIIE protocol, subsequent intentions, and self-efficacy to repeat were related to self-reported tolerance of the intensity of exercise. Methods Using self-reported tolerance of the intensity of exercise, 41 healthy, physically active participants (25 female and 16 male; age 21.3 ± 1.0 years, body mass index 23.0 ± 2.9 kg.m2) were divided into low tolerance (LT, n = 14), middle tolerance (MT, n = 15), and high tolerance (HT, n = 12) groups. Participants completed a 20-min LV-HIIE circuit training video [2 × (10 ×30 s work, 15 s rest)] at home. Participants reported ratings of perceived exertion, affective valence, and perceived activation at baseline, during the protocol, immediately post-protocol, and during the cool down. 20-min after completion, respondents answered questions on exercise task self-efficacy and intentions to repeat LV-HIIE. Results The study recruited n = 65 individuals, of whom n = 50 passed screening. Ultimately n = 41 (82%) completed the exercise protocol and data collection. Ratings of perceived exertion were not significantly different between groups (p = 0.56), indicating similar perceptions of task difficulty. There was no significant effect of tolerance on affective valence (p = 0.36) or felt arousal (p = 0.06). There was evidence of high individual variability in affective responses within and between participants. Subsequent intentions and self-efficacy to repeat the exercise protocol did not seem to be related to affective valence during or after the protocol. Discussion Recruitment and data collection indicated that research into “at home” LV-HIIE is possible. High individual differences in affective responses suggest that LV-HEII may be appropriate for some but not all as an exercise option. Assessing self-reported tolerance of intensity of exercise may not appropriately identify whether or not LV-HIIE will be suitable for an individual.